Barriers in Online Learning Based on the First and Second Graders’ Perspective - Ria Ambarsari; E. Kus Eddy Sartono; Winarni Jhon (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Primary school children in grade 1 and 2 are children who need more attention and guidance from teachers and parents. However, primary school children in grade 1 and 2 faced many challenges in online learning. Therefore, we aimed to explore challenges that 22 primary school children in grade 1 and 2 (7-8 years old) faced in online learning during Covid-19 pandemic in 8 primary schools in Palembang, South Sumatra Province, Indonesia. This research is a qualitative research with a type of phenomenology. We found that first and second grade primary school children faced varied challenges both from the children themselves (internal challenges) and the environment such as parents, teachers and others (external challenges). Hopefully, this research is useful for teachers, principals, other school members and government of Indonesia in gathering information about challenges that happened in online learning during Covid-19 pandemic and its solutions.